1999
DOI: 10.1016/s0043-1354(98)00275-9
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical production of highly effective polyaluminum chloride

Abstract: AbstractÐThis paper presents a new electrolytic method for the synthesis of PAC (polyaluminum chloride). The ECR (electrochemical reactor) used aluminum sheets as anode and AlCl 3 aqueous solution as electrolyte. This method adopted low voltage and high electric current intensity during electrolysis. Some factors of the electrochemistry and the chemistry of the aqueous solution, aecting the formation of the most eective species of PAC, were also studied. The liquid product of PAC, in which the most eective spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 13 publications
2
35
1
1
Order By: Relevance
“…Besides, another PACl (PACl 2 ) was prepared with the method of an electrolysis process [25,26]. Total aluminum concentrations (Al T ) were determined by an inductively coupled plasma optical emission spectrometer (ICP-OES) (Optima 2000, Perkin Elmer, U.K.).…”
Section: Characterization Of Coagulantsmentioning
confidence: 99%
“…Besides, another PACl (PACl 2 ) was prepared with the method of an electrolysis process [25,26]. Total aluminum concentrations (Al T ) were determined by an inductively coupled plasma optical emission spectrometer (ICP-OES) (Optima 2000, Perkin Elmer, U.K.).…”
Section: Characterization Of Coagulantsmentioning
confidence: 99%
“…Lu et al (1999) illustrated the principle of PACl preparation by electrolysis and demonstrated the electrolysis process could provide favorable conditions for polyaluminum formation. The purpose of this investigation is to optimize the Al 13 yield conditions in the electrolysis process for PACl preparation.…”
Section: Introductionmentioning
confidence: 99%
“…PAC always contains a different speciation of hydroxy aluminum (Lu et al, 1999). The study on chemical speciation of aqueous aluminum hydroxyl clusters has achieved significant progress in recent years (Tang, 2006, Sposito, 1997, Their classification could be exemplified in Table 1.…”
Section: Introductionmentioning
confidence: 99%